El principio de causalidad y el concepto de gasto necesario - Villanueva Gutiérrez, Walker (2013)
Could it be stated that the fulfillment of the causality principle is required in order for expense deduction to be applied? And, can criteria such as reasonability and normality be considered complementary to causality in Peruvian domestic law? In the present article, the author analyzes how the causality principle is configured in our legal system, and explains the importance of its subjective and objective division. He also ends up examining the concept of necessary expenditure from, as understood in local and foreign jurisprudence.